2019
DOI: 10.1158/1535-7163.mct-18-0558
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ Blockade Enhances Radiotherapy Abscopal Efficacy Effects in Combination with Anti-PD1 and Anti-CD137 Immunostimulatory Monoclonal Antibodies

Abstract: Radiotherapy can be synergistically combined with immunotherapy in mouse models, extending its efficacious effects outside of the irradiated field (abscopal effects). We previously reported that a regimen encompassing local radiotherapy in combination with anti-CD137 plus anti-PD-1 mAbs achieves potent abscopal effects against syngeneic transplanted murine tumors up to a certain tumor size. Knowing that TGFb expression or activation increases in irradiated tissues, we tested whether TGFb blockade may further e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 54 publications
(76 reference statements)
2
45
0
Order By: Relevance
“…Moreover, the simultaneous blocking of CD47 and PD-1 can further prevent the immune escape of circulating tumor cell subsets, thereby inhibiting metastasis [161,162]. Rodríguez-Ruiz et al proposed that combined anti-PD1 and anti-CD137 treatment increases granzyme-B secreted by CTLs, indicating an improved cytotoxic effect [163]. RANKL, which blocks NF-κB ligands, can increase the anti-metastatic activity of antibodies targeting PD1/PD-L1, and the combination of anti-PD1 and anti-RANKL agents can recruit NK cells to promote the synergy between NK cells and TILs.…”
Section: Combination Therapeutic Strategy To Enhance T Immune Cell Fumentioning
confidence: 99%
“…Moreover, the simultaneous blocking of CD47 and PD-1 can further prevent the immune escape of circulating tumor cell subsets, thereby inhibiting metastasis [161,162]. Rodríguez-Ruiz et al proposed that combined anti-PD1 and anti-CD137 treatment increases granzyme-B secreted by CTLs, indicating an improved cytotoxic effect [163]. RANKL, which blocks NF-κB ligands, can increase the anti-metastatic activity of antibodies targeting PD1/PD-L1, and the combination of anti-PD1 and anti-RANKL agents can recruit NK cells to promote the synergy between NK cells and TILs.…”
Section: Combination Therapeutic Strategy To Enhance T Immune Cell Fumentioning
confidence: 99%
“…Promising results were also seen in metastatic CRC models in which TGFβ inhibition sensitized previously unresponsive tumours to anti-PD1 [ 92 ]. RT-induced TGFβ was shown to inhibit abscopal responses even in combination with anti-PD-1 and anti-CD137 mAbs; this was overcome by TGFβ blockade [ 93 ]. TGFβ blockade has also demonstrated promising results in combination with an agonistic OX40 mAb in metastatic breast cancer, where there was a synergistic T-cell dependent response [ 94 ].…”
Section: The Impact Of Myeloid Cell Populations On Rt and Immunotheramentioning
confidence: 99%
“…Many studies have confirmed the immunomodulatory effects of local therapy; radiotherapy promotes the immunological system by inducing immunogenic cell death and subsequently increasing the sensitivity of lymphocytes to tumor cells [37,[47][48][49][50]. Studies also have demonstrated that the abscopal effect of local treatment combined with immunotherapy enhances the efficacy of treatment for breast cancer cases in animal models [51].…”
Section: Discussionmentioning
confidence: 95%